Ecological and chemical study of Eichhornia Crassipes plant growing in water of Shatt Al-Ksar in Thi Qar - southern Iraq - Hasanain Ali Al-Kinani,; Hussain Alwan Mana, (University of Thi-Qar Journal of agricultural research, 2025)
The results of this study highlight the important ecological role of water hyacinth in aquatic environments, in particular in improving water quality through the absorption of trace elements and organic pollutants. The study samples were collected from Shatt al-ksar during the autumn of 2023,The results of the three sample stations showed noticeable differences in the main physical and chemical parameters , including dissolved oxygen (DO), salinity, electrical conductivity (EC), and total petroleum hydrocarbons (TPH). These variations were closely associated with the density of water hyacinth coverage at each site. Station 1, characterized by dense plant cover, exhibited the lowest DO levels alongside the highest concentrations of trace elements and TPH outcome attributed to increased oxygen consumption from plant biomass decomposition and limited gas exchange due to dense growth. In contrast, Station 2, with moderate vegetation, showed intermediate values. Station 3, which lacked vegetation almost entirely, recorded the highest DO and the lowest levels of EC and TPH, reflecting better water clarity and quality in the absence of plant cover. Furthermore, analysis of pollutant accumulation in different plant parts revealed that the roots and vesicles retained the highest levels of trace elements (Ni, Cr, Cu, Zn, and Pb) and TPH. These results reinforce the effectiveness of water hyacinth in pollutant uptake and stabilization, particularly in areas subject to contamination, underscoring its potential role in phytoremediation applications. As for the chemical composition of the plant, analyses showed a high content of organic matter (with an average exceeding 60% of the dry weight) and varying proportions of fibers, proteins, and ash. This reflects the plant's suitability for use in industrial and agricultural applications. This is consistent with the results of other studies that showed a relative compatibility in the ratios of ash, protein, and humidity. The novelty of this study lies in comparing aquatic sites with different levels of water hyacinth growth, examining vegetation density, water properties, trace element concentrations, and TPH. It analyzes the accumulation of heavy metals and TPH in the different parts of the plant and presents a dual perspective on the role of the water hyacinth as both a pollutant and a sustainable environmental solution.